The effectiveness of training fourth grade students on mental arithmetic strategies in improving their performance in finding the results of arithmetic operations on numbers - Al-Maqbali, Anwaar Sulaiman Ali; Al-Mufarji, Hamida Hamid Khalfan (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to reveal the effectiveness of training fourth grade students at Asmaa bint Amis Basic Education School in Al Dhahirah Governorate on mental arithmetic strategies in improving their performance in finding the results of arithmetic operations on numbers. The study sample consisted of 24 male and female students who are studying in Section 1 of the fourth grade for the academic year 2021/2022 AD. In order to collect the data, a pre- and post-test for the mental arithmetic skill was prepared as a research tool and then applied to the study sample, and after analyzing the data, the results were as follows: A noticeable increase in the average scores of students in the post-test for the mental arithmetic skill, which confirms the effectiveness of training students on strategies Mental arithmetic improves their performance in finding the results of arithmetic operations on numbers. The study concluded with a set of recommendations, the most important of which are:  •Holding training courses for teachers in the second field in which the importance of the mental arithmetic strategies applied in the first episode is focused on and how they can be benefited from and applied. •Creating a guide that includes mental arithmetic strategies applied in the series curriculum for the first episode, explaining through the most important mental arithmetic strategie, how to distribute them to grades 1-4, and how they are taught and applied in classrooms.• The necessity of training and accustoming students to mental arithmetic on a daily basis, without using pen and paper, and exposing them to life activities during the class.
Keywords: mental arithmetic strategies; academic achievement; arithmetic operations